Multidimensional Sustainability Assessment of Maize Farming in Tropical Regions - Yusuf, La Ode Muhammad Iksan; Ma'ruf, Muhammad Imam; Sarinah, Sarinah; Abdur-Rabb, Ahmad Faqhruddin; Darwin, Dirmansyah; Nabila, Asma (Agro Bali : Agricultural Journal, 2026)
This study addresses a critical gap in understanding the multidimensional sustainability of tropical maize farming by simultaneously evaluating economic, ecological, socio-cultural, institutional, technological, and infrastructural dimensions using a Multidimensional Scaling (MDS) approach. Focusing on West Muna Regency, Southeast Sulawesi, Indonesia, data were collected from 150 farmers and 30 farmer group leaders, complemented by secondary sources. The study aims to assess sustainability status, identify sensitive attributes influencing outcomes, and provide evidence-based guidance for interventions. Results show an overall sustainability index of 52.59%, indicating a “moderately sustainable” system, with economic (73.81%), socio-cultural (72.01%), and ecological (55.07%) dimensions performing better than institutional (42.24%), infrastructure (40.28%), and technological (32.15%) dimensions. Leverage analysis identifies 18 key attributes critical to sustainability, highlighting the need for targeted interventions to strengthen institutional frameworks, improve infrastructure, and accelerate technology adoption. Beyond policy generalization, the findings offer practical insights for stakeholders, including development agencies and farmer organizations, to design context-specific, inclusive, and operational strategies that enhance the long-term sustainability of maize farming in tropical regions.